Bioprinting of synthetic cell-like lipid vesicles to augment the functionality of tissues after manufacturing - Thaden, Ole; Schneider, Nicole; Walther, Tobias; Spiller, Erin; Taoum, Alexandre; Göpfrich, Kerstin; Duarte Campos, Daniela Filipa (ACS synthetic biology, 2024)
Bioprinting is an automated bioassembly method that enables the formation of human tissue-like constructs to restore or replace damaged tissues. Regardless of the employed bioprinting method, cells undergo mechanical stress that can impact their survival and function postprinting. In this study, we investigate the use of a synthetic cell-like unit, giant unilamellar vesicles (GUVs), as adjuvants of the cellular function of human cells postprinting, or in future as the complete replacement of human cells. We analyzed the impact of two nozzle-based bioprinting methods (drop-on-demand and extrusion bioprinting) on the structure, stability, and function of GUVs. We showed that over 65% of the GUVs remain intact when printing at 0.5 bar, demonstrating the potential of using GUVs as a synthetic cell source. We further increased the stability of GUVs in a cell culture medium by introducing polyethylene glycol (PEG) into the GUV lipid membrane. The presence of PEG, however, diminished the structural properties of GUVs postprinting, and reduced the interaction of GUVs with human cells. Although the design of PEG-GUVs can still be modified in future studies for better cell-GUV interactions, we demonstrated that GUVs are functional postprinting. Chlorin e6-PEG-GUVs loaded with a fluorescent dye were bioprinted, and they released the dye postprinting only upon illumination. This is a new strategy to deliver carriers, such as growth factors, drugs, nutrients, or gases, inside large bioprinted specimens on a millimeter to centimeter scale. Overall, we showed that printed GUVs can augment the functionality of manufactured human tissues.